The Relationship between Parenting Patterns, Parental Smoking Behavior, and Parental Communication on Smoking Behavior among Adolescents - Putri, Suraya; Juwita, Ratna; Hartaty, Neti; Hidayati, Husna (Indonesian Journal of Global Health Research, 2024)
Smoking is a serious global public health issue, especially in low-income countries, including Indonesia, where the prevalence of smoking among adolescents has reached alarming levels. This study aims to analyze the relationship between parenting patterns, parental smoking behavior, and parental communication on adolescent smoking behavior. Using an analytical observational method and a cross-sectional design, data were collected from 60 male students at a high school in Aceh. The results indicate that democratic parenting styles, parental smoking behavior, and effective communication are significantly related to the risk of smoking among adolescents. Adolescents raised in family environments with open communication and positive parenting styles have a lower risk of smoking. These findings underscore the importance of parental roles in preventing smoking behavior among adolescents and recommend interventions focusing on raising parental awareness of the impact of their behavior on their children.